30,000 Minimum Wages: The Economic Effects of Collective Bargaining Extensions - Pedro S. Martins (Institute for the Study of Labor (IZA), 2014)
Several countries extend collective bargaining agreements to entire sectors, therefore binding non-subscriber workers and employers. These extensions may address coordination issues but may also distort competition by imposing sector-specific minimum wages and other work conditions that are not appropriate for many firms. In this paper, we analyse the impact of such extensions along several margins drawing on firm-level monthly data for Portugal, a country where extensions have been widespread until recently. We find that both formal employment and wage bills in the relevant sector fall, on average, by 2% and by 25% more across small firms over the four months after an extension is issued. These results are driven by both reduced hirings and increased firm closures. On the other hand, informal work, not subject to labour law or extensions, tends to increase. Our findings are robust to several checks, including a falsification exercise based on extensions that were announced but not implemented.
Keywords: J31; J52; J23; 330; collective agreements; worker flows; wage rigidity